Investigation of mechanical properties of epoxy resins and random fibre epoxy systems by means of destructive and non-destructive tests. (13th February 2006) - Prassianakis, I.N.; Kytopoulos, V.; Sideridis, E.
In the present experimental work an epoxy resin and a random fibre reinforced epoxy resin system was studied, for the determination of some mechanical properties using destructive and non-destructive tests. Firstly the velocities of elastic waves and the acoustic attenuation coefficient α were evaluated. Then, using these quantities, the elastic modulus, E, the shear modulus, G, the Poisson ratio, ν, and the damage parameter D were evaluated. These properties were correlated with the corresponding properties determined for same materials by using destructive tests. Finally, for an epoxy resin system, the effect of the plasticiser content and the fibres on the moisture absorption behaviour were investigated. In this context, it was shown that the moisture absorption test based on diffusion (mass transport) mechanisms can be used as a non-destructive test for 'intrinsic' (microstructural) damage evaluations in the polymeric system.